Role of Local Governments in Rural Development of Nigeria, A Case Study of Ekwusigo Local Government Area of Anambra State - Ezeamama, Ifeyinwa; Anthony Ofozoba, Chinonso (British Journal of Marketing Studies, 2023)
The study analyzed the role of Local Governments in rural development of Nigeria, a case study of Ekwusigo Local Government Area of Anambra State The objective of the study were to Evaluate the contribution of local government to agricultural development in Ekwusigo Local Government in Anambra State. Examine the role of local government on infrastructural development in Ekwusigo Local Government in Anambra State. Assess the contributions of local government on employment creation Ekwusigo Local Government in Anambra State. Three research hypothesis and three research questions are formulated in line with the above objectives of the study. Descriptive survey design method was used; the sample techniques employed was simple random sampling. The study selected Ekwusigo Local Government Area, the population are 99242 where the sample size is 398 using Taro Yamane formula. The researcher distributes Three hundred and ninety-eight (398) questionnaires but only three hundred and forty-seven (347) copies of questionnaire were retrieved. Structured questionnaire was use to gather information from the population. Percentage tables and ANOVA method of data analysis was used to test the questionnaire. The finding of the study shows that; Local government has made significant contributions to agricultural development in Ekwusigo Local Government in Anambra State. Local government has contributed to infrastructural development in Ekwusigo Local Government in Anambra State. Local government has made significant contributions to employment creation in Ekwusigo Local Government in Anambra State. The study recommended that more concerted efforts should be made toward development of rural areas. These should include increase in budget allocation, effective policy implementation and completion. Corruption and mismanagement of resources should also be discouraged by punishing officials engaged in associated corrupt cats and blocking channels of diverting resources through effective budget planning and monitoring.